Intangibles and industry concentration Supersize me - Bajgar, Matej (OECD Publishing, 2021)
This paper presents new evidence on the growing scale of big businesses in the United States, Japan, and Europe. It finds broad evidence of rising industry concentration across the majority of countries and sectors over the period 2002 to 2014. Rising concentration is strongly associated with intensive investment in intangibles, particularly innovative assets, software, and data. This relationship appears to be stronger in more globalised and digital-intensive industries. The results are consistent with intangibles disproportionately benefiting large firms and enabling them to scale up and increase market shares. We find nuanced implications of these new business models for competition - rising markups and reduced churning amongst the top firms, but falling industry prices
Keywords: Science and Technology